Summary of Alternative Cooling Procedures for Large Bone-In Hams - Chad Carr; Larry Eubanks (EDIS, 2010)
AN247, a 4-page fact sheet by Chad Carr and Larry Eubanks, discusses cooling requirements for heavier weight hams to avoid bacterial contamination. Includes references. Published by the UF Department of Animal Science, July 2010.